2011
DOI: 10.4103/0974-8520.85719
|View full text |Cite
|
Sign up to set email alerts
|

A review on role of prakriti in aging

Abstract: Ayurveda is an eternal science with absolute principles, and prakriti is one of these. It plays an important role in the selection and establishment of every factor for which a person is going to interact from conception till death, e.g. lifestyle, diet planning, etc. Prakriti stands for nature of the body in terms of dosha and is decided at the time of conception according to the predominance of dosha. It does not change during the whole life and is responsible for the physical and mental characteristics of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Similarly certain types of diseases are very common in younger and older age. This concept is called as vayoanupatinee Prakriti [24] , [25] . Hence, the age may have a profounding effect on metabolic expression that can't be assessed in present setup and needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly certain types of diseases are very common in younger and older age. This concept is called as vayoanupatinee Prakriti [24] , [25] . Hence, the age may have a profounding effect on metabolic expression that can't be assessed in present setup and needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Pitta -dominant individuals tend to experience more ulcers, bleeding disorders, and skin diseases [22]. In aging investigations, Pitta -dominant individuals had a higher basal metabolic rate and energy usage which predisposes such individuals to greater tissue loss and premature aging compared to Kapha individuals who tended toward delayed aging [23]. Studies correlating metabolic differences among Prakruti types with metabolic markers have revealed that Pitta -dominant individuals are fast- and Kapha-dominant individuals are slow-metabolizers based on drug metabolizing enzyme markers.…”
Section: Discussionmentioning
confidence: 99%
“…Mental and physical ill-health weakens dhatusamya (homeostasis), resulting in Akalaja vriddhavastha (pathological aging) [61] , [62] , [66] . Ayurveda takes a holistic approach toward the maintenance of dhatusamya , a state of equilibrium of normal anatomical, biological, physiological, mental and spiritual well-being [66] , [67] . Hence a balanced state ( sama ) of tissue ( dhatu ), energy systems ( Dosha ), heat of transformation ( Agni ) and metabolic wastes ( mala ) constitute homeostasis in Ayurveda that leads to healthy aging ( Sukhayu/Kalaja Vriddhavastha ) [66] , [68] .…”
Section: Ayurveda and Science Of Agingmentioning
confidence: 99%
“…Prakruti refers to the biological constitution (anatomical, physiological and psychological) of an individual. The Prakruti which is unique to each individual reflects the baseline characteristics of the individual including metabolism, mental makeup, immunity, inherent strength and weakness and proclivities [67] , [70] , [71] . Thus, Prakruti determines an individual's capacity for transformation at the physical, mental and emotional levels owing to the interactions with internal and external stimuli all of which affect the aging process [63] , [72] .…”
Section: Ayurveda and Science Of Agingmentioning
confidence: 99%